Tackling the Crises (with and within Critical Theory) (KULT_online, 2018)
The volume Critical Theory in Critical Times. Transforming the Global Political & Economic Order, edited by Penelope Deutscher and Cristina Lafont, re-emphasizes the link between critical theory and crisis. Eleven contributions by prominent scholars of critical theory show how political, economic or legal crises make critical theory necessary and how it can serve to explain and critically address the current multiple crises. In doing so, critical theory is undergoing a selfcritique. That, in order to provide accurate diagnoses and responses to current crises, critical theory has to open for different approaches, such as feminist or postcolonial theory, is one outcome of several essays in the volume. At the same time there is a plea for sticking to the core concepts of materialist critique that should not be replaced but rather complemented by these “newer” approaches.